Market Leadership in Multistage Games With Sequences of Technological Races - Flavio Delbono (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1986)
Most of the existing literature on the relationshipbetween market structure and technological competition may be classified according to the way in which the following features are modelled: (i) type of R&D competition; (ii) number of types of players; (iii) number of stages of the game.
Keywords: 330